2016
DOI: 10.1111/are.13138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary phosphorus on growth, body composition and immunity of young taimenHucho taimen(Pallas, 1773)

Abstract: The effects of dietary phosphorus (P) on growth, body composition and immunity of young taimen (Hucho taimen) were studied. Six purified diets contained graded levels (2.3-control, 4.0, 5.6, 7.5, 9.1 and 10.8 g kg À1 diet) of available P. Each diet was fed to triplicate groups of 30 fish with an initial average weight (55.31 AE 0.38) g for 84 days. The weight gain, specific growth rate and feed conversion ratio were improved by dietary available P up to 4.35 g kg À1 (P < 0.05) and then levelled off. Hepatosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 62 publications
(87 reference statements)
5
11
0
Order By: Relevance
“…The highest growth was observed in the D4 and D5 groups that received over 7.6 g/kg AP. This result was consistent with many previous results showing that reduced growth rate or feed utilization was the main deficiency signs of P (Borlongan & Satoh, ; Liang, Liu, Tian, Yang, & Liang, ; Luo, Tan, Liu, & Wang, ; Schamber et al., ; Shen et al., ; Wang et al., ; Xie et al., ; Yao et al., ; Ye et al., ). However, other researchers suggested that the growth of fish was not affected by different levels of dietary AP (Baeverfjord, Asgard, & Shearer, ; Chaimongkol & Boonyaratpalin, ; Fontagné et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The highest growth was observed in the D4 and D5 groups that received over 7.6 g/kg AP. This result was consistent with many previous results showing that reduced growth rate or feed utilization was the main deficiency signs of P (Borlongan & Satoh, ; Liang, Liu, Tian, Yang, & Liang, ; Luo, Tan, Liu, & Wang, ; Schamber et al., ; Shen et al., ; Wang et al., ; Xie et al., ; Yao et al., ; Ye et al., ). However, other researchers suggested that the growth of fish was not affected by different levels of dietary AP (Baeverfjord, Asgard, & Shearer, ; Chaimongkol & Boonyaratpalin, ; Fontagné et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…Crucian carp ( Carassius auratus ) is one of the most widely cultured fish in China (Chiu et al., ). Although many research studies on the P requirement of various kinds of cultured fish have been conducted (Deschamps, Poirier Stewart, Demanche, & Vandenberg, ; Nwanna, Kühlwein, & Schwarz, ; Prabhu, Schrama, & Kaushik, ; Shen et al., ; Wang et al., ; Xie et al., ), there are very few studies on the optimal available P (AP) requirement for this fish (Chen, Sun, Kong, Tang, & Gan, ). This study was aimed to evaluate the growth performance, body composition and blood chemistry of crucian carp under different dietary P levels in order to determine the dietary AP requirement of the fish.…”
Section: Introductionmentioning
confidence: 99%
“…SOD activity affected by dietary P has been evaluated in many studies. Inhibited plasma SOD activity was also found in hybrid sturgeon ( ♀Huso huso × ♂Acipenser schrenckii ) and young taimen ( Hucho taimen ) after feeding low P diet (Jin et al, ; Wang et al, ). In the present study, fish in the low P groups (0 and 50 mg P/kg BW) showed inhibited ALP and SOD activity, indicating that fish were suffering oxidative stress because of the P deficiency.…”
Section: Discussionmentioning
confidence: 96%
“…Disturbance of P homeostasis in fish could induce significant physiological effects on fish including oxidative stress (Jin et al, ; Skonberg et al, ). Thus, fish would be susceptible to the outside environment such as pathogens or contaminants at the status of the disturbed homeostasis because of the inappropriate P addition in the diet (Chen et al, ; Sugiura et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the P requirement in animals diverge depending on the response parameters evaluated and the models used to estimate the requirement [6]. For instance, P requirement based on weight gain are lower than those estimated based on bone mineralization [710]. The use of P requirement estimates based on WG have led to several bone deformities in salmonids imposing a threat to the welfare of fish and the quality of the final product [1012].…”
Section: Introductionmentioning
confidence: 99%